On the torsional and coupled torsion-tension/compression behavior of magnesium alloy solid rod: A crystal plasticity evaluation - Wang, Huamiao; Zhang, Xiaodan; Wu, Wei; Liaw, Peter K.; An, Ke; Yu, Qin; Wu, Peidong (International journal of plasticity, 2022)
•The torsional and coupled torsion-tension/compression behaviors of magnesium alloy solid rod are systematically investigated through experiments and the crystal plasticity model.•Torsional behavior and the resultant Swift effect depend strongly on the texture.•The axial stress would affect the twinning activities drastically in different loadings.•The difference between shears and torsion is attributed to the significant bulk stress caused by the strong interaction between the cylindrical elements. Extensive attention has been paid to magnesium (Mg) alloys considering their potential as lightweight structural materials. However, it is still challenging to process and manufacture Mg materials that carry high strength and good ductility. This issue mainly arises from a lack of understanding toward the anisotropic mechanical behavior of Mg alloys in response to large deformation in a multiaxial stress state, which is unavoidably in existence under various material processing routes. In this regard, we seek to understand the torsional and coupled torsion-tension/compression behaviors of a magnesium alloy subject to large-strain deformation. The elastic viscoplastic self-consistent (EVPSC) model, which incorporates the twinning-detwinning (TDT) scheme and takes a torsion-specific finite element (TFE) approach, was employed to illuminate the inhomogeneous and multiaxial features of the torsional deformation in the AZ31 Mg alloy subjected to free/fixed-end torsion and coupled torsion-tension/compression. Experimental validation was conducted by characterizing the mechanical responses of the torsional specimens under the loading paths of free-end torsion and coupled torsion-tension. Our model successfully captures the Swift effect along with the shear texture, which is hardly predicted by conventional constitutive models. In addition, our model reveals that twinning is nearly equally active under free-/fixed-end torsion, while twinning under coupled torsion-tension and torsion-compression is promoted and suppressed, respectively. The comparison between the simple shear and pure torsion by simulation demonstrates that the significant bulk stress existing within the torsional rod is ascribed to the strong interaction between the cylindrical elements in the EVPSC model. As a final thought, we believe that the TFE-EVPSC-TDT model not only highlights the inhomogeneous and multiaxial features underlying the torsional and coupled torsion-tension/compression behaviors of the Mg alloy solid rod, but more significantly, can be used as a numerical tool for designing/tuning gradient twinning structures that may lead to optimized properties of Mg alloys.